An Experimental Study of Chlorite Stability in Varied Subduction Zone Lithologies with Implications for Fluid Production, Melting, and Diapirism in Chlorite-Rich Mélange Rocks. (30th March 2022) - Lakey, Shayne; Hermann, Jörg
Abstract: Four ultramafic bulk compositions comprising only natural minerals were used to constrain the stability field of chlorite in a variety of subducted, chlorite-rich rocks through an examination of key chlorite dehydration reactions relevant to the sub-arc. Seventy-four piston cylinder experiments were conducted at a range of pressures (1.0–5.0 GPa) and temperatures (500°C–1150°C). Bulk 1 represents a chlorite mélange (Mg# = 0.94) typically formed in the subduction channel. This composition was used to examine the terminal chlorite reactions to olivine, orthopyroxene, and spinel at low pressure and to olivine, garnet, and spinel at high pressure. Chlorite achieves a thermal maximum stability at 2.0 GPa, 850°C; at 3.0 GPa, 850°C; and at 5.0 GPa, 760°C. The terminal chlorite breakdown reaction rises at a much steeper Clapeyron slope than shown in previous studies. Bulk 2 contains additionally antigorite and tremolite, to constrain phase relations in more fertile compositions. Chlorite reacts with clinopyroxene at ~100°C lower temperatures and with orthopyroxene at ~20°C–60°C lower temperatures than the terminal chlorite breakdown. The reactions have a subparallel Clapeyron slope and none of the three chlorite dehydration reactions crosses the antigorite breakdown reaction up to 5 GPa. This demonstrates that chlorite is the most stable carrier of H2 O to high temperatures in subducted ultramafic rocks. Chlorite mélanges that form at the subduction plate interface will dehydrate at 850°C–800°C, 80–120 km depth for intermediate to hot subduction geotherms and liberate 10–12 wt.% of H2 O, triggering wet melting in associated sediments. For cold subduction geotherms, chlorite dehydration occurs at 780°C–740°C, 120–170 km depth. Interaction of such fluids with sediments will likely produce a supercritical fluid phase. No melting in the ultramafic rocks has been observed at the chlorite breakdown reactions. Wet melting of the chlorite mélange at 3 GPa occurred between 1100°C and 1150°C. The stability of chlorite in more Fe-rich mélanges (bulk Mg# = 0.50 and 0.68, respectively) were conducted at 3.0 GPa and revealed thermal maxima at 650°C and 765°C, respectively. Collectively, the thermal stability of chlorite is dependent upon the Mg# of the bulk composition and spans over 200°C at sub-arc depths. The density of run products was calculated to test the validity of the chlorite mélange diapir model. With the progressive breakdown of chlorite, ultramafic chlorite mélanges transform into garnet peridotite, thereby losing any buoyancy they initially possessed. This makes the likelihood of mélange diapirs as a major transport mechanism through the sub-arc unfeasible.